Marriage Function as Protection Rights Against Wife and Children Right in Polygamous Marriage - Muhammad Madih; I Dewa Putu Gede Anom Danujaya; Munsharif Abdul Chalim (Jurnal Akta, 2019)
Marriage is a bond between man and woman which is also the religion of Islam is a way of worship, that in the community there is monogamy: one husband and one wife, but there are also polygamous marriage is one man with more than one wife with their applicable laws and regulations for implementation. The purpose of this study was to: 1) To determine the function of the marriage covenant can provide legal protection of the rights wife and children in polygamous marriages. 2) To determine the right of wife and children in polygamous marriages. 3) To know the legal remedies can be done to determine the rights of wives and children in polygamous marriages. Based on the results of data analysis concluded that: 1) The function of the marriage contract may provide legal protection of the rights of the wife and children in polygamous marriages as a certainty or limitation of rights received by his wife and children during the marriage took place and as a measure for husbands to act fairly in polygamous marriages , 2) The position of the right wife and children in polygamous marriages, namely the right wife by the husband proportionate balanced well after their second marriage and so are the rights of children still get their right in accordance with the provisions of the Act. 3) Remedies that can be done to determine the right istir and children in polygamous marriages with authentic mating agreements made governing the boundary between the rights and obligations of husband and wife in a polygamous marriage.Keywords: Marriage; Polygamy; Marriages Agreement; Wife and Children's Rights.